Determinants of Garlic Producers Market Outlet Choices in Goncha Siso Enese District, Northwest Ethiopia: A Multivariate Probit Regression Analysis - Fasika Chekol; Teshager Mazengia (Advances in Agriculture)
This study investigates the factors influencing garlic producers’ market outlet selection decisions in Goncha Siso Enese District, Ethiopia. A total of 359 garlic producer households were polled, and the results were analyzed using a multivariate probit (MVP) model. According to the MVP model results, extension contact, access to market information, quantity of garlic sold, and farm experience in farming were negatively and significantly associated with the choice of consumer outlet. Besides this, the estimated MVP for retailer outlet choice is positively influenced by the amount of quantity sold, and farm experiences in garlic have a significant and positive effect on the choice of retailer outlets. In contrast, education level, access to credit, extension contact, and land area allocated for garlic have a negative influence on the choice of retail outlet. Moreover, wholesaler outlet choice is significantly and positively influenced by education level, access to credit, amount of quantity sold, extension contact, and distance to market, whereas it is negatively influenced by lagged price. Assembler outlet is also positively influenced by sex, distance to market, access to market information, and quantity sold, and negatively affected by extension contact and lag price. The implication is that, if smallholder garlic producers have access to alternative market outlets, they must select an appropriate combination of market outlets to maximize their income in the long run. It is suggested that equal access to marketing infrastructure in potential production areas, the garlic production system, and rural-urban development infrastructure should be improved and made more accessible.